PEMBUATAN POSTER INFOGRAFIS SEBAGAI INOVASI PENYAJIAN PROFIL DESA YANG INFORMATIF DAN MENARIK: STUDI DI DESA BAMBAPULA KABUPATEN TOLITOLI - Husna Annur; Mohammad Sawir; Mohammad Rosid (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Referring to the Minister of Home Affairs Regulation No. 12 of 2007, village profiles are an important tool for accurately determining the potential and level of development of an area. Based on this understanding, the State Administration Study Program at Madako University Tolitoli, through its 2025 community service activities, took the initiative to assist Bambapula Village, North Dampal District, Tolitoli Regency in compiling a village profile. This profile is designed to describe the general conditions of the village as stipulated in the aforementioned Minister of Home Affairs Regulation. The methods used in implementing this community service activity include observation and planning, implementation, submission, and evaluation. The objective of creating an infographic poster of the Bambapula Village profile is to increase the target audience's knowledge of the Bambapula Village profile, thereby supporting transparency in the information system in Bambapula Village. The result of this community service activity is an informative visual medium that has been adapted to the latest data in an attractive style that is easy for the target audience to understand.